2021
DOI: 10.3390/vaccines9070750
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Conformational Stabilization of a HIV-1 Clade C Consensus Envelope Trimer Immunogen Impacts the Profile of Vaccine-Induced Antibody Responses

Abstract: Stabilization of the HIV-1 Envelope glycoprotein trimer (Env) in its native pre-fusion closed conformation is regarded as one of several requirements for the induction of neutralizing antibody (nAb) responses, which, in turn, will most likely be a prerequisite for the development of an efficacious preventive vaccine. Here, we systematically analyzed how the stepwise stabilization of a clade C consensus (ConC) Env immunogen impacts biochemical and biophysical protein traits such as antigenicity, thermal stabili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Interestingly, shifting of Env-specific antibody responses away from V3 through concealment or elimination has been achieved, but was not accompanied by an increased production of Tier 2 neutralizing Abs (35,45). In line, studies into stepwise conformational stabilization of Env trimer immunogens demonstrated a decline of V3 reactivity with increasing trimer stabilization, yet also with declining overall Env immunogenicity and V2 responses 27 . These findings, in combination with our results, suggest that a strong V3 response does not negatively interfere with antibody responses to other Env regions and therefore the pursuit of inducing of bNAbs and binding antibodies against regions of putative viral vulnerability does not have to be mutually exclusive.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Interestingly, shifting of Env-specific antibody responses away from V3 through concealment or elimination has been achieved, but was not accompanied by an increased production of Tier 2 neutralizing Abs (35,45). In line, studies into stepwise conformational stabilization of Env trimer immunogens demonstrated a decline of V3 reactivity with increasing trimer stabilization, yet also with declining overall Env immunogenicity and V2 responses 27 . These findings, in combination with our results, suggest that a strong V3 response does not negatively interfere with antibody responses to other Env regions and therefore the pursuit of inducing of bNAbs and binding antibodies against regions of putative viral vulnerability does not have to be mutually exclusive.…”
Section: Discussionmentioning
confidence: 88%
“…The peptide microarray used in our study, manufactured by JPT (Berlin, Germany), was designed to map IgG recognition of linear HIV-1 Env regions in preclinical and clinical vaccine studies and has been described previously ( 27 ). The array consists of 1034 15mer peptides with an 11 amino acid overlap to cover the whole gp160 extracellular domain of the HIV-1 Env.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CD4-bound conformation has not been widely explored, particularly in terms of immunogen development, as prefusion (ligand-free) states are known to favour neutralizing antibodies epitopes [34] , [35] , including conformational ones [9] , [36] while non-neutralizing antibodies sometimes target epitopes exposed upon CD4 binding such as the CD4-induced (CD4i) and the crown of the third hypervariable (V3) loop [37] , [38] epitopes. As such, immunogen development strategies have sought to maximize prevention of immunodominant (neutralization-hypersensitive) regions, targets of non-neutralizing antibodies, by engineering Envs with increasing mutations for structural stability of the trimer in its native state with much reduced CD4 affinity [39] , [40] . While it cannot be argued that the preferential antigenic properties of these improved trimers have been finely mapped and their improved immunogenicity in preclinical studies well demonstrated [11] , [41] , the limitations of focusing on the closed, ligand-free trimer as an immunogen have been highlighted here and in other studies [21] .…”
Section: Discussionmentioning
confidence: 99%